Nontrivial Solutions for Periodic Schrödinger Equations with Sign-Changing Nonlinearities. (15th January 2015) - Chen, Shaowei; Lin, Lishan; Xiao, Liqin
Abstract : We prove a new infinite-dimensional linking theorem. Using this theorem, we obtain nontrivial solutions for strongly indefinite periodic Schrödinger equations with sign-changing nonlinearities.